O território na construção de dois museus em Santo Tirso. O Museu Municipal Abade Pedrosa e o Museu Internacional de Escultura Contemporânea - João Miguel Pinho Marques Monteiro Figueiras (2022)
The present dissertation has as object of study the Abade Pedrosa Municipal Museum (MMAP) and the International Museum of Contemporary Sculpture (MIEC). This academic work aims to understand the relationships that these two museums establish between themselves, with their immediate surroundings and with the territory in which they are located. The intentions and motivations that led to the rehabilitation of the MMAP in the monastery wing and the construction of the new volume, the MIEC, will be dissected. Given the intrinsic relationship between museums and territory; the MMAP in the former hostel of the monastery, and the MIEC as a synthesis of the symposia that take place throughout the city, the dissertation is crossed by the analysis of place. As such, this dissertation begins with an analysis and study of the place, where the museums are located, in the city of Santo Tirso. The reasons that lead the monastery, the first building to be constructed in this zone, to be implanted in that place are analysed and in which way it influences other constructions and contiguous spaces, as it is the case of the hospice of the monastery, the square Abade Pedrosa and the chapel of Senhor dos Passos. The analysis extends to the development of the city, which always starts from the monastery. Then, the contemporary sculpture symposiums which were the driving force behind the creation of the current International Museum of Contemporary Sculpture are dealt with. In this way, it was important to understand the origin of these symposia and what their intentions and objectives were, as well as the transformations operated by this project in the green spaces of Santo Tirso. Once again, the relationship with the place and the territory stands out, being this the main and transversal theme in this dissertation, which is also addressed at the scale of architecture when studying the two museums made by the architects Álvaro Siza and Eduardo Souto de Moura. At this point we study the implantation, the organization and the relation with the nearby surroundings and the neighbouring buildings. Finally, we also speculate on the relationship between place, architecture and sculpture and how they can co-exist and relate to each other. This is an innovative approach since museums have never been studied from the point of view proposed.